The Effect of the Project-Based Learning Model on Science Learning Outcomes of Fifth-Grade Students at MIN 1 Musi Banyuasin - Tamsiyati, Eti Tamsiyati; Tiara Nadila; Yasmini, Evi; Ismail, Fajri; Efriani, Arvin (The Future of Education Journal, 2024)
This study aims to analyze the effect of the Project Based Learning (PBL) model on the science learning outcomes of fifth-grade students at MIN 1 Musi Banyuasin. The research uses a quantitative approach with a pre-experimental design, specifically the one-group pretest-posttest design. The study population consists of all fifth-grade students at MIN 1 Musi Banyuasin for the 2024/2025 academic year, totaling 90 students, with a sample of 30 students from class V-A selected using simple random sampling. The research instrument is a multiple-choice test consisting of 23 validated items to assess science learning outcomes. Data analysis was conducted using paired t-test at a 5% significance level. The results show a significant effect of implementing the Project Based Learning model on science learning outcomes, as evidenced by a t-value of 15.427 and a significance value of 0.000 < 0.05. The average learning outcomes increased from 62.33 on the pretest to 82.67 on the posttest, with an improvement of 20.34 points. This study concludes that the Project Based Learning model is effective in improving the science learning outcomes of fifth-grade students at MIN 1 Musi Banyuasin.